METHODOLOGY FOR COST ESTIMATION OF TOPOGRAPHIC, GEODETIC, AND CARTOGRAPHIC WORKS - Korenets, Oleksandr; Pidlisetska, Iryna; Bulgakov, Andrii; Kurach, Tamara (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
B a c k g r o u n d . The issue of economic evaluation of topographic, geodetic, and cartographic works (hereinafter – TG&CW) within Ukraine's defence sector remains insufficiently addressed in current scientific research. In the context of security and defence sector reform, and in light of the growing demand for geospatial support to military operations, there is a pressing need for a scientifically grounded methodology for determining the cost of TG&CW. This methodology should reflect the operational specifics of the Topographic Service of the Armed Forces of Ukraine (TS AFU). The proposed cost estimation model consists of six stages: data preparation, core calculation procedures, determination of direct and indirect expenses, calculation of baseline estimated cost, coordination, and approval of cost estimates.M e t h o d s . The article applies general scientific methods such as analysis, comparison, synthesis, analogy, the systems approach, and structural-graphic modelling. These methods allowed for the systematisation of existing approaches to cost assessment in TG&CW and facilitated the development of a structured graphical model for calculating their cost.R e s u l t s . The developed system of baseline calculation indicators includes labour costs, material expenditures, transportation costs, equipment costs and depreciation, administrative and overhead expenses, as well as allowances for unforeseen expenses and operational risks. There is both a scientific and practical need for an economic-methodological model for assessing TG&CW costs, adapted to the structure and missions of the TS AFU. Such a model would serve as a basis for managerial decision-making in planning, logistics, and resource allocation.C o n c l u s i o n s . The proposed structural-graphic model for cost estimation accounts for the military-specific context of TG&CW, integrating a comprehensive system of cost indicators including labour, material, transportation, administrative, and overhead expenses. A key outcome of this study is the development of a system of baseline calculation indicators, which may be adapted to various types of TG&CW conducted by the TS AFU.
Keywords: topographic, geodetic, and cartographic works, economic evaluation, Topographic Service, cost estimation, structural model, geospatial data